Comparison of pulmonary vein isolation using cryoballoon, high-power short-duration, and conventional radiofrequency ablation for atrial fibrillation: a propensity score-weighted study - Park, Hanjin; Park, Je-Wook; Kim, Daehoon; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Hwang, Chun; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2023)
Background The comparative efficacy, saftey, and heart rate variability (HRV) parameters after pulmonary vein isolation using cryoballoon (Cryo-PVI), high-power short-duration (HPSD-PVI), and conventional radiofrequency ablation (conventional-PVI) for atrial fibrillation (AF) is unclear. Materials and methods In this propensity score-weighted, retrospective analysis of a single-center cohort, we analyzed 3,395 patients (26.2% female, 74.5% paroxysmal AF) who underwent AF catheter ablation without an empirical left atrial ablation. Procedural factors, recurrence rates, complication rates, and the post-procedural HRV parameters were compared across the Cryo-PVI (n = 625), HPSD-PVI (n = 748), and conventional-PVI (n = 2,022) groups. Results Despite the shortest procedural time in the Cryo-PVI group (74 min for Cryo-PVI vs. 104 min for HPSD-PVI vs. 153 min for conventional-PVI, p < 0.001), the major complication (p = 0.906) and clinical recurrence rates were similar across the three ablation groups (weighted log-rank, p = 0.824). However, the Cryo-PVI group was associated with a significantly lower risk of recurrent AF in patients with paroxysmal AF [weighted hazard ratio (WHR) 0.57, 95% confidence interval (CI) 0.37–0.86], whereas it was associated with a higher risk of recurrent AF in patients with persistent AF (WHR 1.41, 95% CI 1.06–1.89, p for interaction of <0.001) compared with the conventional-PVI group. In the subgroup analysis for the HRV, the Cryo-PVI group had the highest low-frequency-to-high-frequency ratio at 1-year post-procedure, whereas the HPSD-PVI group had the lowest low-frequency-to-high-frequency ratio at 1-year post-procedure (p < 0.001). Conclusions The Cryo-PVI group had better rhythm outcomes in patients with paroxysmal AF but worse rhythm outcomes in patients with persistent AF and a higher long-term post-procedural sympathetic nervous activity and sympatho-vagal balance compared with the conventional-PVI group.